Penerapan Model UTAUT untuk Mengetahui Minat Perilaku Konsumen dalam Penggunaan QRIS - Putri Nur Auliya; Muhammad Fikry Arransyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Technological advances in the payment system have replaced the role of cash into a more efficient and economical form of non-cash payment. Currently, there are more and more technologies that affect the payment system with a variety of applications that people use as a means of non-cash payment. Therefore, on 17 August 2019 Bank Indonesia released a Quick Response (QR) Code standard for payments through server-based electronic money applications, electronic wallets, or mobile banking called the QR Code Indonesian Standard (QRIS). This study aims to determine the factors that influence behavioral intention to use QRIS by using theoryModel Unified Theory of Acceptance and Use Technology (UTAUT). The research method used is descriptive quantitative. Sampling technique is done by using the technique nonprobability sampling that is purposive sampling with a sample of 100 respondents from QRIS users. The results of this study show performance expectancy, effort expectancy, and social influence has a positive and significant influence on behavioral intention the use of QRIS. Behavioral intention has a positive and significant influence on use behavior. Whereas, facilitating conditions has a positive and not significant effect on use behavior the use of QRIS.